Economic relations with newly industrialising countries - Dietrich Kebschull (Intereconomics, 1983)
It is often maintained, with reference to the increasing competition from newly industrialising countries, that Western support for the development of LDCs' economies would only amount to supplying the rope with which one will later be hanged. Our author argues that, contrary to that opinion, the coming into existence of NICs should be looked upon not as a threat, but as a chance for improvement of the international division of labour and for further growth.
Keywords: 330; NICs